Multi-layer film, adhesive film, decorative film, decorative adhesive film, and protective film for automobiles
A multilayer film using polyolefin resin and silicone-olefin copolymer addresses compatibility and environmental issues, offering excellent scratch resistance and flexibility for three-dimensional applications, enhancing processability and suitability for automotive use.
Patent Information
- Application Number
- JP2021044320
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-26
- Filing Date
- 2021-03-18
- Publication Date
- 2024-12-23
- Estimated Expiration
- 2041-03-18
AI Technical Summary
Existing adhesive films face issues with poor compatibility between plasticizers and adhesives, leading to stability problems and environmental concerns, while coatings for scratch resistance and flexibility are inefficient and difficult to apply to three-dimensional shapes.
A multilayer film composed of polyolefin resin and silicone-olefin copolymer, with specific ratios and layers, providing excellent scratch resistance, flexibility, and conformability to three-dimensional shapes, and allowing for adhesive or printed layers to be laminated.
The film achieves high scratch resistance, flexibility, and conformability to complex shapes, with improved processability and reduced environmental impact, suitable for automotive applications.
Smart Images

Figure 0007604281000001 
Figure 0007604281000002 
Figure 0007604281000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an industrial adhesive film (tape), a decorative adhesive film (tape) such as a sticker, label, or marking film that is attached to a signboard, automobile, or the like to impart design, a multilayer film with excellent scratch resistance that is preferably used for a decorative sheet, etc., and an adhesive film in which an adhesive layer is laminated onto the film. [Background technology]
[0002] Conventionally, films made of polyvinyl chloride resin (hereinafter also referred to as "PVC-based films"), which have excellent colorability, processability, scratch resistance, weather resistance, etc., have been widely used as the substrate for industrial adhesive films (tapes), decorative adhesive films (tapes) such as stickers, labels, and marking films that are affixed to signs, automobiles, etc. to impart design features, and decorative sheets, etc. The PVC film itself has rigidity, but a plasticizer is added to impart flexibility so that the film can function as an adhesive film. However, depending on the plasticizer used, the film may have poor compatibility with the adhesive, resulting in poor stability when used as an adhesive film, and the plasticizer may bleed out significantly. In addition, there is a tendency for restrictions on the use of plasticizers to be strengthened. Therefore, polyolefin resin films have come to be widely used as an alternative to PVC films.
[0003] Adhesive films such as marking films that use a polyolefin resin film as a substrate are well known. In response to the demand for a film with appropriate flexibility, an adhesive film is known in which an elastomer component is blended into the substrate and an acrylic-modified urethane coating is further laminated onto the substrate, thereby improving scratch resistance and durability (Patent Document 1). Furthermore, proposals have been made regarding laminated films suitable for various applications, including marking films, which use polyolefin-based resins with excellent flexibility, have high gloss, and have good scratch resistance, ability to conform to curved surfaces, and ease of application (Patent Documents 2 and 3). Furthermore, a film in which a silicone-olefin copolymer is contained in a polyolefin resin has been proposed with the aim of obtaining a molded article with excellent stain resistance (Patent Document 4).
[0004] However, the techniques described in Patent Documents 1 to 3 rely on coating to provide performance, which poses problems such as environmental issues due to drying and volatilization of the solvent, poor management and economic efficiency due to an increase in the number of processes, etc. In addition, the coating films described in Patent Documents 1 to 3 have a crosslinked structure, which causes problems such as poor conformability to the shape of the molded body to be bonded and poor elongation. Regarding Patent Document 4, although the use of a silicone-olefin copolymer improves the antifouling properties and surface slipperiness, the polyolefin resin used is hard and has a high melting point, and therefore there is an issue with its conformability to molded articles having three-dimensional shapes. Therefore, there is still room for improvement from the perspective of environmental issues, process simplification, and application to molded bodies with three-dimensional shapes. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2004-2825 A [Patent Document 2] JP 2007-83530 A [Patent Document 3] Patent No. 5112646 [Patent Document 4] JP 2017-206587 A DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]
[0006] In view of the above-mentioned problems, the present invention has an object to provide a polyolefin resin multilayer film having excellent scratch resistance, flexibility and ability to conform to a molded article having a three-dimensional shape. Another object of the present invention is to provide a polyolefin-based resin multilayer film that has the above-mentioned characteristics and can also be used to obtain adhesive films or decorative films by laminating an adhesive layer or a printed layer onto the film, and that can be suitably used for automotive decorative applications. [Means for solving the problem]
[0007] Means for Solving the Problems The present inventors have conducted extensive research and have found that the above-mentioned problems can be solved by a polyolefin-based resin film having a layer made of a resin composition containing a predetermined amount of a polyolefin-based resin and a silicone-olefin copolymer on at least one of the front and back sides, the polyolefin-based resin film having a tensile modulus within a specific range, thereby completing the present invention.
[0008] That is, the gist of the present invention is as follows. [1] A multilayer film having a plurality of layers containing a polyolefin resin, A layer made of a resin composition containing 0.20 parts by mass or more of a silicone-olefin copolymer per 100 parts by mass of a polyolefin resin is provided on at least one of the front and rear surfaces, The multilayer film is characterized in that the multilayer film has a tensile modulus of elasticity of 400 MPa or less. [2] The multilayer film according to [1], characterized in that a silicone-olefin copolymer masterbatch containing the silicone-olefin copolymer is used as the silicone-olefin copolymer. [3] The multilayer film according to [1] or [2], characterized in that it is composed of at least two layers. [4] The multilayer film according to any one of [1] to [3], characterized in that the polyolefin resin contains one or more of a polyethylene resin, a polypropylene resin, and an olefin elastomer. [5] The multilayer film according to any one of [1] to [4], wherein each layer of the multilayer film contains 50 parts by mass or more of an olefin-based elastomer per 100 parts by mass of a polyolefin-based resin. [6] At least one layer of the multilayer film contains 50 parts by mass or more of an olefin-based elastomer per 100 parts by mass of a polyolefin-based resin; The multilayer film according to any one of [1] to [4], wherein the layer made of the resin composition contains 5 to 50 parts by mass of an olefin-based elastomer per 100 parts by mass of a polyolefin-based resin. [7] The multilayer film according to [6], comprising at least a surface layer, an intermediate layer and a back layer, wherein the surface layer and the back layer contain 1 part by mass or more and 80 parts by mass or less of an olefin-based elastomer per 100 parts by mass of polyolefin-based resin, the intermediate layer contains 50 parts by mass or more and 100 parts by mass or less of an olefin-based elastomer per 100 parts by mass of polyolefin-based resin, and at least one of the surface layer and the back layer is a layer made of a resin composition containing 0.20 parts by mass or more of a silicone-olefin copolymer per 100 parts by mass of polyolefin-based resin. [8] The multilayer film according to any one of [1] to [7], which has a 60° gloss value of 60 or more after a Gakushin abrasion test. [9] An adhesive film comprising the film according to any one of items [1] to [8] and an adhesive layer laminated on at least one surface of the film.
[10] A decorative film comprising the film according to any one of items [1] to [8] and a printed layer laminated on at least one surface of the film.
[11] A decorative adhesive film obtained by laminating an adhesive layer on the printed layer side of the decorative film described in
[10] .
[12] A protective film for automobiles, which uses the film according to any one of [9] to
[11] . Effect of the Invention
[0009] In the present invention, by using a film having a layer made of a resin composition containing a predetermined amount of a polyolefin resin and a silicone-olefin copolymer, a multilayer film having excellent scratch resistance, flexibility, and conformability to a molded body having a three-dimensional shape can be obtained. In addition, by laminating an adhesive layer or a printed layer on the film, it is also possible to obtain an adhesive film, a decorative film, or a decorative adhesive film, and these films can be suitably used for automotive cosmetic applications. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The present invention will be described in detail below, but the present invention is not limited to the following embodiments and can be modified and practiced in various ways within the scope of the gist. In addition, when the expression "~" is used in this specification, it is used as an expression including the numerical value or physical property value before and after it.
[0011] One embodiment of the present invention is a multilayer film having a plurality of layers containing a polyolefin resin, characterized in that the multilayer film has a layer made of a resin composition containing 0.20 parts by mass or more of a silicone-olefin copolymer per 100 parts by mass of polyolefin resin on at least one of the front and back sides, and the tensile modulus of the multilayer film is 400 MPa or less (hereinafter also referred to as the "multilayer film of the present invention").
[0012] <Polyolefin resin> The resin composition used in the present invention contains a polyolefin resin and a silicone-olefin copolymer as essential components (hereinafter, this resin composition will be referred to as "resin composition A").
[0013] From the viewpoints of resin availability, flexibility, ease of handling, and economic efficiency, polyolefin resins are preferably used.
[0014] Examples of polyolefin resins include polyethylene resins, polypropylene resins, olefin elastomers, and cyclic olefin resins. Among the polyolefin resins, polyethylene resins, polypropylene resins, and olefin elastomers are preferred from the viewpoints of availability and imparting flexibility to the resulting film.
[0015] Examples of polyethylene resins include ethylene homopolymers, copolymers of ethylene mainly composed of ethylene and other monomers copolymerizable therewith (low-density polyethylene (LDPE), high-pressure low-density polyethylene, linear low-density polyethylene (LLDPE), high-density polyethylene (HDPE), ethylene copolymers obtained by polymerization using a metallocene catalyst (metallocene-based polyethylene), ethylene-vinyl acetate copolymers, ethylene-methyl (meth)acrylate copolymers, ethylene-ethyl (meth)acrylate copolymers, ethylene-butyl (meth)acrylate copolymers, ethylene-(meth)acrylic acid copolymers, and metal ion crosslinked resins (ionomers) of ethylene-(meth)acrylic acid copolymers. Of these, it is preferable to use low density polyethylene (LDPE) and linear low density polyethylene (LLDPE) from the viewpoints of availability, ease of handling of the resin, and imparting flexibility to the resulting film.
[0016] Examples of polypropylene-based resins include homopolymers of propylene (homopolypropylene), copolymers containing propylene as the main component and other monomers copolymerizable with propylene, and mixtures of these. Examples of the copolymers containing propylene as a main component and other monomers copolymerizable with propylene include random copolymers (random polypropylenes) and block copolymers (block polypropylenes) of propylene and ethylene or other α-olefins, and block or graft copolymers containing a rubber component.
[0017] The α-olefin used as the other monomer copolymerizable with propylene preferably has 4 to 12 carbon atoms, and examples thereof include 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 4-methyl-1-pentene, and 1-decene. One or a mixture of two or more of these is used.
[0018] The olefin-based elastomer is a soft resin containing a polyolefin-based resin and a rubber component, and may be one in which the rubber component is dispersed in the polyolefin-based resin, or one in which the two are copolymerized with each other. Specific examples of olefin-based elastomers include amorphous elastic copolymers mainly composed of olefins, such as ethylene-propylene copolymer elastomers, ethylene-1-butene copolymer elastomers, ethylene-propylene-1-butene copolymer elastomers, ethylene-1-hexene copolymer elastomers, ethylene-1-octene copolymer elastomers, ethylene-styrene copolymer elastomers, ethylene-norbornene copolymer elastomers, propylene-1-butene copolymer elastomers, ethylene-propylene-non-conjugated diene copolymer elastomers, ethylene-1-butene-non-conjugated diene copolymer elastomers, and ethylene-propylene-1-butene-non-conjugated diene copolymer elastomers, as well as derivatives and acid-modified derivatives thereof. Olefin elastomers are classified into reactor type, simple blend type, dynamic crosslinking type, etc. according to the production method, but the reactor type is preferred because the domain diameter of the dispersed rubber component is small and transparency is high. Specific examples of reactor type olefin elastomers include "Wellnex (manufactured by Japan Polypropylene Corporation)", "Zelas (manufactured by Mitsubishi Chemical Corporation)" and "Catalloy (manufactured by Sunallomer Co., Ltd.)".
[0019] The polyethylene resin, polypropylene resin, and olefin elastomer described above may be used alone or in combination of two or more. From the viewpoint of the flexibility of the obtained film and the film formability when processed into a film, it is preferable to use two or more of them in combination.
[0020] The melt flow rate of the polyolefin resin is appropriately selected depending on the molding method and application, but is preferably 0.1 to 50 g / 10 min as measured at a temperature of 190° C. or 230° C. and a load of 2.16 kg. If it is 0.1 g / 10 min or more, the moldability of the film is good, and if it is 50 g / 10 min or less, the thickness precision of the film can be maintained at a good level. It is more preferably 0.5 to 40 g / 10 min, and even more preferably 1.0 to 30 g / 10 min.
[0021] Regarding the strength of the polyolefin resin, the tensile modulus of a film made of the polyolefin resin alone is preferably within the range of 100 to 2000 MPa. If the tensile modulus is within the range of 100 to 2000 MPa, it is possible to impart appropriate flexibility to the film obtained from the resin composition of the present invention. It is more preferably within the range of 150 to 1900 MPa, and even more preferably within the range of 200 to 1800 MPa. In addition, from the viewpoint of the flexibility and processability of the obtained multilayer film, it is preferable that the elastic modulus of the polyolefin resin is 400 MPa or less.
[0022] Each layer of the multilayer film of the present invention, other than the layer made of resin composition A, is made of a polyolefin resin composition containing a polyolefin resin (hereinafter also referred to as "polyolefin resin composition B"). The type of polyolefin resin contained in each of these layers may be one type or two or more types. In addition, the blending ratio of the polyolefin resin composition B constituting each of these layers may be the same or different.
[0023] From the viewpoint of imparting flexibility to the multilayer film of the present invention, it is preferable to add an olefin-based elastomer to the resin compositions used in each layer of the multilayer film (i.e., resin composition A and the polyolefin-based resin composition B). Furthermore, in order to impart sufficient flexibility to the multilayer film, the proportion of the olefin-based elastomer in the polyolefin-based resin used in each layer of the multilayer film is more preferably 50 parts by mass or more, and even more preferably 60 parts by mass or more.
[0024] As another method for imparting flexibility, in at least one layer of the multilayer film, the proportion of the olefin-based elastomer added to the polyolefin-based resin composition B is 50 parts by mass or more and 100 parts by mass or less, and the proportion of the olefin-based elastomer added to the resin composition A is 1 part by mass or more and 80 parts by mass or less, thereby imparting flexibility to all layers. In one embodiment of the multilayer film of the present invention, at least one layer of the multilayer film contains 50 parts by mass or more of an olefin-based elastomer per 100 parts by mass of a polyolefin-based resin, and the layer made of resin composition A contains 5 to 50 parts by mass, preferably 5 to 40 parts by mass, and more preferably 5 to 30 parts by mass of an olefin-based elastomer per 100 parts by mass of a polyolefin-based resin.
[0025] Another method of imparting flexibility to a multilayer film having at least a surface layer, an intermediate layer, and a back layer is to add an olefin-based elastomer to the composition (resin composition A, and optionally a polyolefin-based resin composition B) used for the surface layer and the back layer of the multilayer film in an amount of 1 part by mass or more and 80 parts by mass or less, and add an olefin-based elastomer to the composition (above-mentioned polyolefin-based resin composition B) used for the intermediate layer of the multilayer film in an amount of 50 parts by mass or more and 100 parts by mass or less, thereby imparting flexibility to all layers. Here, at least one of the surface layer and the back layer is a layer made of resin composition A containing 0.20 parts by mass or more of silicone-olefin copolymer per 100 parts by mass of polyolefin-based resin. It is more preferable that the proportion of the olefin-based elastomer in the front and back layers is 5 parts by mass or more and 70 parts by mass or less, and that the proportion of the olefin-based elastomer in the intermediate layer is 60 parts by mass or more and 100 parts by mass or less. The proportion of polyolefin-based elastomer in the front and back layers is 80 parts by mass or less, which prevents the film from sticking to the roll during production. The proportion of polyolefin-based elastomer in the middle layer is 50 parts by mass or more, which gives the multi-layer film sufficient flexibility.
[0026] As resins other than the above-mentioned polyethylene-based resin, polypropylene-based resin, and olefin-based elastomer, styrene-based elastomer, cyclic olefin-based resin, etc. may also be added as necessary.
[0027] The styrene-based elastomer is preferably a block copolymer represented by the following formula (I) or (II). X-(YX)n …(I) (XY)n …(II) In general formulas (I) and (II), X is an aromatic vinyl polymer block typified by styrene, and in formula (I), the degree of polymerization at both ends of the molecular chain may be the same or different. Y is at least one selected from a butadiene polymer block, an isoprene polymer block, a butadiene / isoprene copolymer block, a hydrogenated butadiene polymer block, a hydrogenated isoprene polymer block, a hydrogenated butadiene / isoprene copolymer block, a partially hydrogenated butadiene polymer block, a partially hydrogenated isoprene polymer block, and a partially hydrogenated butadiene / isoprene copolymer block. n is an integer of 1 or more.
[0028] Examples of cyclic olefin resins include norbornene polymers, vinyl alicyclic hydrocarbon polymers, and cyclic conjugated diene polymers. Among these, norbornene polymers are preferred. Examples of norbornene polymers include ring-opening polymers of norbornene monomers and norbornene copolymers obtained by copolymerizing norbornene monomers with α-olefins such as ethylene. Hydrogenated products of these may also be used.
[0029] <Silicone-olefin copolymer> Resin composition A used to produce the multilayer film of the present invention contains a polyolefin resin and a silicone-olefin copolymer as essential components. A silicone-olefin copolymer is used to impart excellent scratch resistance and slipperiness to the resulting multilayer film while maintaining good processability during film formation of the multilayer film. Silicone-olefin copolymers have excellent compatibility with the polyolefin resins mentioned above, which makes it possible to prevent defects caused by bleed-out on the surface of the resulting film and to impart long-term scratch resistance and slipperiness.
[0030] The silicone-olefin copolymer used in the present invention is a copolymer containing silicone (a polymeric compound containing a siloxane bond) and olefin (or polyolefin). The silicone-olefin copolymer used in the present invention may be a graft copolymer in which a polyolefin is grafted onto silicone, or a graft copolymer in which a silicone block is grafted onto polyolefin, or a block copolymer in which a polyolefin block is covalently bonded to a silicone block may be used. From the viewpoints of availability and compatibility with polyolefin resins, it is preferable to use a block copolymer.
[0031] The amount of silicone-olefin copolymer added in the resin composition A is preferably 0.20 parts by mass or more relative to 100 parts by mass of the polyolefin resin described above. By making it 0.20 parts by mass or more, it is possible to impart excellent scratch resistance and slipperiness to the obtained multilayer film. It is more preferably 0.25 parts by mass or more, and even more preferably 0.30 parts by mass or more.
[0032] In order to further improve compatibility and dispersibility with polyolefin resins, it is preferable to use a masterbatch in which the silicone-olefin copolymer described above is dispersed in advance in a polyolefin resin at a high concentration. The polyolefin resin used in the master batch may be the same as that described above.
[0033] The content of the silicone-olefin copolymer in the master batch is preferably 5 parts by mass or more and 80 parts by mass or less. By making it 5 parts by mass or more, it is possible to provide a sufficient amount of the silicone-olefin copolymer to exhibit scratch resistance, and by making it 80 parts by mass or less, it is preferable because the processability when pelletizing the master batch is less impaired. More preferably, it is 10 parts by mass or more and 70 parts by mass or less, and even more preferably, it is 20 parts by mass or more and 60 parts by mass or less.
[0034] Specific examples of masterbatches containing silicone-olefin copolymers include "EXFORA (manufactured by Mitsui Fine Chemicals Co., Ltd.)", "X-22-2101", "X-22-2125H", "X-22-2138B" (all manufactured by Shin-Etsu Chemical Co., Ltd.), "BY27-001", and "BY27-201" (all manufactured by DuPont Toray Specialty Materials Co., Ltd.).
[0035] <Ultraviolet absorbing agent> As the ultraviolet absorbing agent, known agents can be used, and examples thereof include benzotriazole-based ultraviolet absorbing agents, benzophenone-based ultraviolet absorbing agents, and triazine-based ultraviolet absorbing agents. Examples of the benzophenone-based ultraviolet absorbers include 2,2'-dihydroxybenzophenone-based ultraviolet absorbers such as 2,2'-dihydroxy-4-methoxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, and 2,2',4,4'-tetrahydroxybenzophenone; 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-n-octoxybenzophenone, 2-hydroxy-4-methoxy-2'-carboxybenzophenone, 2-hydroxy-4-benzoyloxybenzophenone, 2-hydroxy-5-chlorobenzophenone, and 2-hydroxy-4-methoxy-5-sulfonebenzophenone; 2,4-dihydroxybenzophenone; and bis-(2-methoxy-4-hydroxy-5-benzoylphenyl)methane. Examples of benzotriazole-based ultraviolet absorbers include 2-[2'-hydroxy-3'-(3",4",5",6"-tetrahydrophthalimidomethyl)-5'-methylphenyl]benzotriazole (molecular weight 388), 2-[2-hydroxy-3,5-bis(α,α-dimethylbenzyl)phenyl]-2H-benzotriazole (molecular weight 448), and 2,2-methylenebis[4-(1,1,3,3-tetramethylbutyl-6-(2H-benzotriazol-2-yl)phenol] (molecular weight 659). Examples of triazine-based ultraviolet absorbers include 2,4-bis(2,4-dimethylphenyl)-6-(2-hydroxy-4-n-octyloxyphenyl)-1,3,5-triazine, 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-((hexyl)oxy)-phenol, 2-(4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl)-5-(octyloxy)phenol, 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-(octyloxy)phenol, 2-(4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl)-5-(hexyloxy)phenol, and 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-((methyl)oxy)phenol. Among these, triazine-based ultraviolet absorbents are preferred because they have excellent ability to absorb high-energy, short-wavelength ultraviolet rays.
[0036] The ultraviolet absorbing agent may be added to all layers of the multilayer film, or may be added to only some of the layers (for example, the front and back layers). The amount of the ultraviolet absorber is not particularly limited, and may be within a range that does not blow out from the film. The ultraviolet absorber is contained in an amount of 0.01 to 10 parts by mass, preferably 0.05 to 9 parts by mass, and particularly preferably 0.1 to 0.5 parts by mass, relative to 100 parts by mass of the polyolefin resin composition in each layer of the multilayer film. By containing 0.01 parts by mass or more of the ultraviolet absorber, deterioration of the multilayer film of the present invention due to ultraviolet rays can be prevented, so that excellent scratch resistance and slipperiness can be maintained for a long period of time. In addition, by setting the upper limit to 10 parts by mass or less, the ultraviolet absorber does not bleed out from the multilayer film, and deterioration due to ultraviolet rays can be sufficiently prevented, so that excellent scratch resistance and slipperiness can be maintained for a long period of time while maintaining the appearance of the film.
[0037] Examples of ultraviolet absorbents include BASF's "Tinuvin 326," "Tinuvin 234," and "Tinuvin 1600," and ADEKA's "LA31RG." From the viewpoint of ultraviolet absorption ability at low wavelengths, BASF's "Tinuvin 1600" is preferred. Masterbatches containing added ultraviolet absorbers are also commercially available, such as "TX1897D" manufactured by Japan Polypropylene and "MKV7722" manufactured by Dainichi Seikagaku Kagaku Co., Ltd., and from the viewpoint of low wavelength ultraviolet absorption ability, "MKV7722" manufactured by Dainichi Seikagaku Kagaku Co., Ltd. is preferred.
[0038] <Light stabilizer> As the light stabilizer, a known one can be used, and examples thereof include hindered amine light stabilizers. Examples of the hindered amine light stabilizer include 2,2,6,6-tetramethylpiperidinyl-4-benzoate, bis(2,2,6,6-tetramethyl-4-piperidinyl)sebacate, tris(2,2,6,6-tetramethyl-4-piperidinyl)phosphite ("Chimasorp 944" manufactured by BASF Ltd.), 1,3,8-triaza-7,7,9,9-tetramethyl-3-n-octylpyro[4,5]decane-2,4-dione (manufactured by BASF Ltd.), and 1,3,8-triaza-7,7,9,9-tetramethyl-3-n-octylpyro[4,5]decane-2,4-dione (manufactured by BASF Ltd.). Examples of such tert-butyl ethers include "Tinuvin 144" manufactured by Epson Corporation), 1,2,3,4-tetra(4-carbonyloxy-2,2,6,6-tetramethylpiperidinyl)-butane, 1,3,8-triaza-7,7,9,9-tetramethyl-2,4-dioxo-spiro[4,5]decane, tri(4-acetoxy-2,2,6,6-tetramethylpiperidinyl)amine, 4-stearoyloxy-2,2,6,6-tetramethylpiperidine, 4-benzyloxy-2,2,6,6-tetramethylpiperidine, 4-phenylcarbamoyloxy-2,2,6,6-tetramethylpiperidine, 4-p-toluenesulfonyloxy-2,2,6,6-tetramethylpiperidine, and bis(2,2,6,6-tetramethyl-4-piperidinyl)terephthalate, which may be used alone or in combination of two or more.
[0039] The hindered amine light stabilizer may be added to all layers of the multilayer film, or may be added to only some of the layers (for example, the front and back layers). The amount of the hindered amine light stabilizer is preferably 0.01 to 10 parts by mass per 100 parts by mass of the resin in each layer. If the amount is 0.01 part by mass or more, a stabilizing effect is easily obtained, and if the amount is 10 parts by mass or less, an effect commensurate with the amount is obtained and there is no risk of blooming.
[0040] Masterbatches containing added light stabilizers are also commercially available. Examples of such masterbatches include "MBU10A" manufactured by Japan Polypropylene, "LX1004" manufactured by Japan Polyethylene, and "XJ100H" manufactured by Japan Polyethylene. From the viewpoint of dispersibility with polypropylene-based resins and olefin-based elastomers, "MBU10A" manufactured by Japan Polypropylene is preferred. The light stabilizer can be used in combination with an ultraviolet absorber. It is preferable to use them in combination, and the synergistic effect of using them in combination is expected to provide better weather resistance than when the light stabilizer and the ultraviolet absorber are added alone.
[0041] <Other ingredients> In addition to the polyolefin resin and silicone-olefin copolymer described above, various additives may be blended into the resin composition used in the multilayer film of the present invention in order to impart heat resistance, weather resistance, and the like. Specific examples of the additives that may be used include antistatic agents, antioxidants, neutralizing agents, lubricants, antiblocking agents, plasticizers, heat stabilizers, dyes and pigments, crystal nucleating agents, fillers, inorganic fillers that impart rigidity, and elastomers other than those mentioned above that impart flexibility, within the scope of not impairing the effects of the present invention.
[0042] As the antistatic agent, a known one can be used, but it is preferable to use a polymeric antistatic agent in order to impart long-term antistatic properties to the film and to suppress problems caused by bleeding out to the surface.Specific examples of the polymeric antistatic agent include known ones, such as a block copolymer of a hydrophobic block and a hydrophilic block, and examples of the block copolymer formed by the hydrophobic block and the hydrophilic block through an ester bond, an ether bond, an amide bond, an imide bond, a urethane bond, and a urea bond.
[0043] <Multi-layer film> The multilayer film of the present invention is a multilayer film having a layer made of a resin composition A containing 0.20 parts by mass or more of a silicone-olefin copolymer per 100 parts by mass of a polyolefin resin on at least one of the front and back sides. From the viewpoint of the handleability of the obtained film, the tensile modulus of the multilayer film is required to be 400 MPa or less. By making it a multilayer film rather than a single layer, it becomes possible to add silicone-olefin copolymer to either or both of the front and back layers, which makes it possible to impart scratch resistance and slipperiness to either or both of the front and back layers while preventing the addition of excessive silicone-olefin copolymer, which is also effective from an economic standpoint.
[0044] In addition, the multilayer film of the present invention is preferably a film consisting of at least three layers consisting of a front and back layer and an intermediate layer. By adding a silicone-olefin copolymer to one of the front and back layers, it is possible to impart scratch resistance and slipperiness to only one side. In addition, by adding a silicone-olefin copolymer to the front and back layers, it is possible to impart scratch resistance and slipperiness to both sides of the multilayer film. Whether the silicone-olefin copolymer is added to only one of the front and back layers or to the front and back layers can be appropriately selected in consideration of the use and processability of the multilayer film to be used. When an adhesive layer, a printed layer, or the like is provided on one side of the obtained multilayer film, it is preferable not to add a silicone-olefin copolymer to the front layer or back layer on the side on which the adhesive layer or printed layer of the multilayer film is provided, from the viewpoint of adhesion between those layers and the multilayer film.
[0045] The multilayer film of the present invention is required to have a tensile modulus of 400 MPa or less when measured using a test piece (JIS K 6732) taken from the film in an atmosphere of 23 ° C. and 50% RH with a tensile tester at a tensile speed of 50 mm / min according to JIS K 7161. By making it 400 MPa or less, it is possible to maintain good processability when laminating an adhesive layer or a printed layer on the multilayer film, and good handleability when laminating a multilayer film having an adhesive layer to an article having a three-dimensional shape such as an automobile exterior. More preferably, it is 380 MPa or less, and even more preferably, it is 360 MPa or less. The tensile modulus of the obtained multilayer film can be adjusted by adjusting the above-mentioned polyethylene-based resin, polypropylene-based resin, olefin-based elastomer, styrene-based elastomer, cyclic olefin-based resin, etc.
[0046] From the viewpoint of scratch resistance and slipperiness, the multilayer film of the present invention preferably has a 60° gloss value of 60 or more after the Gakushin abrasion test. If the 60° gloss value is 60 or more, sufficient gloss is maintained even after the test, and it can be judged to have good scratch resistance and slipperiness. More preferably, it is 65 or more, and even more preferably, it is 70 or more. In addition, it is preferable that the 60° gloss value retention rate before and after the Gakushin abrasion test, which is represented by the following formula, is 60% or more. If the 60° gloss value retention rate is 60% or more, it can be judged to have good scratch resistance and slipperiness as described above. More preferably, the 60° gloss value retention rate is 65% or more, and even more preferably, it is 70% or more. TIFF0007604281000001.tif15169
[0047] The conditions for the Gakushin abrasion test of the present invention are based on JIS K5701-1, in which a cotton cloth is attached to a 20 mm square friction element, a load of 500 g is applied, and the multilayer film surface is then moved back and forth 10 times.
[0048] As a method for forming the film, a known method can be used, but it is preferable to use a melt extrusion method. Among the melt extrusion methods, a T-die molding method in which a molten resin is extruded from an extruder having a T-die and cooled and solidified to obtain a film is more preferable. In order to obtain a multilayer film, it is preferable to use a co-extrusion T-die molding method using multiple extruders. Examples of the co-extrusion T-die molding method include a method in which multiple resin layers are formed into a film using a multi-manifold die, and then the layers are brought into contact in a T-die to obtain a film, and a method in which multiple resins are brought into contact with each other using a device that combines molten resins called a feed block, and then a multilayer film is obtained.
[0049] If necessary, one or both sides of the multilayer film may be subjected to a surface treatment such as a plasma treatment, a corona treatment, an ozone treatment, a flame treatment, etc. Depending on the application of the resulting film, it is possible to select whether to perform the surface treatment on one or both sides.
[0050] The thickness of the multilayer film is not particularly limited, but is preferably 30 to 400 μm. By keeping the thickness within the above range, the film can be maintained in a good condition for handling and subsequent processability. The thickness is more preferably 50 to 350 μm, and even more preferably 70 to 300 μm. In addition, the thickness of the front layer or back layer of the multilayer film is preferably within the range of 5 to 40% of the total thickness of the multilayer film. By making it 5% or more, it is possible to sufficiently impart the scratch resistance and slipperiness of the silicone-olefin copolymer described above to the front layer or back layer. By making it 40% or less, it is preferable from the viewpoint of film formability and economic efficiency when obtaining a multilayer film. It is more preferably within the range of 5 to 35%, and even more preferably within the range of 5 to 30%.
[0051] The elongation of the film is preferably 100% or more when measured using a test piece (JIS K 6732) taken from the film in accordance with JIS K 7161 at a tensile tester under an atmosphere of 23°C and 50% RH at a tensile speed of 300 mm / min. If the tensile elongation at break is 100% or more, problems due to breakage of the film when the film is taken up during melt extrusion molding can be suppressed, and similar problems can also be suppressed in the subsequent process of laminating a printing layer and an adhesive layer, so this is preferable. It is more preferably 150% or more, and even more preferably 200% or more.
[0052] The multilayer film of the present invention has high transparency and a good appearance when laminated to an article such as an automobile outer layer by setting the haze value to 8% or less when measured by a method conforming to JIS K7136 using a Haze Meter NDH2000 manufactured by Nippon Denshoku Industries Co., Ltd., after applying liquid paraffin to the film to eliminate unevenness. The haze value is more preferably 6% or less, and even more preferably 4% or less.
[0053] The multilayer film of the present invention is required to be weather resistant because it is used by laminating articles such as the outer layer of an automobile. 2 The cycle of irradiation (63°C, 50%) for 102 minutes and irradiation + rainfall (40°C, 95%) for 18 minutes is preferably performed, and the embrittlement time is preferably 200 hours or more, more preferably 250 hours or more, and even more preferably 300 hours or more. The embrittlement of the multilayer film was evaluated by whether it broke when bent 180°. If the treatment time for embrittlement was 300 hours or more, it was judged as ◯; if it was 200 hours or more but less than 300 hours, it was judged as △; if it was less than 200 hours, it was judged as ×.
[0054] <Adhesive film> The multilayer film of the present invention can be made into an adhesive film by laminating an adhesive layer on at least one surface of the multilayer film of the present invention (hereinafter also referred to as "adhesive film of the present invention").
[0055] The adhesive used as the adhesive layer is not particularly limited, and various adhesives such as natural rubber resins, acrylic resins, styrene resins, silicone resins, polyvinyl ether resins, etc. may be used. In addition, a functional layer such as an adhesive layer or a thermosetting resin layer may be further provided on the adhesive layer. In the pressure-sensitive adhesive film of the present invention, the above-mentioned surface treatment may be performed on one or both sides of the film before laminating the pressure-sensitive adhesive layer. In addition, a primer layer may be provided between the multilayer film of the present invention, which is the base film, and the pressure-sensitive adhesive layer, if necessary. The thickness of the adhesive layer and the primer layer can be appropriately determined according to need.
[0056] <Decorative film> The multilayer film of the present invention can be used as a decorative film by laminating a printed layer on at least one surface thereof (hereinafter also referred to as "the decorative film of the present invention"). The printed layer constituting the decorative film can be formed by a known method. For example, known printing methods such as offset printing, gravure rotary printing, and screen printing, known coating methods such as roll coating and spray coating, and flexographic printing can be used. Vapor deposition can also be used. Examples of print patterns include wood grain, stone grain, cloth grain, sand grain, geometric patterns, letters, full solid patterns, metallic patterns, and the like. The thickness of the printing layer can be appropriately determined according to need. In the decorative film of the present invention, the above-mentioned surface treatment may be performed on one or both sides of the film before laminating the printed layer. In addition, a primer layer may be provided between the multilayer film of the present invention, which serves as a base film, and the printed layer, if necessary. The thickness of the printing layer and the primer layer can be appropriately determined according to need.
[0057] <Cosmetic adhesive film> If necessary, the decorative film of the present invention can be made into a decorative adhesive film by further laminating an adhesive layer on the printed layer (hereinafter also referred to as "the decorative adhesive film of the present invention"). By adhering this decorative adhesive film to an adherend, it is possible to impart a beautiful appearance to the adherend, making it possible to use it for decorative applications in the interior and exterior of automobiles, other molded bodies and laminates, and for interior and exterior building applications, etc. That is, one aspect of the present invention is an automobile protective film using the pressure-sensitive adhesive film of the present invention, the decorative film of the present invention, or the decorative pressure-sensitive adhesive film of the present invention.
[0058] The multilayer film of the present invention has excellent scratch resistance, flexibility, and conformability to a molded body having a three-dimensional shape. Furthermore, it is possible to obtain an adhesive film or a decorative film by laminating an adhesive layer or a printed layer on the film, and these films can be suitably used for automotive decorative purposes. EXAMPLES
[0059] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to these examples. The materials used in the following examples and comparative examples and the methods for measuring the evaluated properties are as follows.
[0060] [Materials used] <Polyolefin resin (PO resin)> Random polypropylene (A): Japan Polypropylene, "FW4B" (random polypropylene, melt flow rate at 230°C and 2.16 kg = 8.0 g / 10 min, melting point = 136°C, tensile modulus of film alone = 600 MPa) Random polypropylene (B): SunAllomer Corporation, "PC630A" (random polypropylene, melt flow rate at 230°C and 2.16 kg = 7.5 g / 10 min, melting point = 142°C, tensile modulus of film alone = 600 MPa) Linear low density polyethylene: "0540F" manufactured by Ube Maruzen Polyethylene Co., Ltd. (metallocene-catalyzed linear low-density polyethylene, melt flow rate at 190°C and 2.16 kg = 4 g / 10 min, melting point = 87°C and 111°C, tensile modulus of the film alone = 100 MPa) Olefinic elastomers: Japan Polypropylene, "Wellnex RFX4V" (olefin elastomer, melt flow rate at 230°C and 2.16 kg = 6.0 g / 10 min, melting point = 127°C, tensile modulus of film alone = 230 MPa) Using a differential scanning calorimeter (Mettler Toledo DSC823e), each polyolefin was Approximately 5 mg of fin-based resin was heated from 25°C to 230°C at a heating rate of 10°C / min, and then The temperature is lowered to 25°C at a cooling rate of 10°C / min, and then increased again to 230°C at a heating rate of 10°C / min. The melting peak temperature measured on the chart was taken as the melting point.
[0061] <Silicone-olefin copolymer masterbatch> Mitsui Fine Chemicals, Inc.'s "EXFOLA PP2000" (master batch consisting of 30 parts by mass of silicone-olefin copolymer (a block copolymer of silicone and polyolefin components) and 70 parts by mass of homopolypropylene; melt flow rate at 230°C and 2.16 kg = 20.0 g / 10 min)
[0062] <Slip agent masterbatch> Japan Polypropylene Corporation's "MBS05A" (polypropylene slip agent masterbatch containing 5 parts by mass of fatty acid amide)
[0063] <Ethylene-HALS copolymer high molecular weight light stabilizer> "XJ100H" (a polyethylene-based light stabilizer containing 5 parts by mass of a hindered amine-based light stabilizer) manufactured by Japan Polyethylene Corporation
[0064] <Light stabilizer masterbatch> Japan Polypropylene Corporation's "MBU10A" (polypropylene-based light stabilizer masterbatch containing 10 parts by mass of hindered amine light stabilizer)
[0065] <UV absorber masterbatch A> Japan Polypropylene Corporation's "TX1897D" (polypropylene-based UV absorber masterbatch containing 5 parts by mass of benzotriazole-based UV absorber) <UV absorber masterbatch B> Dainichi Seika Chemicals Co., Ltd., "MKV7722" (polypropylene-based UV absorber masterbatch containing 5 parts by mass of triazine-based UV absorber)
[0066] <Preparation of Resin Composition> The above polyolefin resins were mixed by dry blending in a total amount of 100 parts by mass, and the other materials were the raw materials and additive amounts shown in Table 1. It was confirmed by visual inspection that the mixture was uniformly mixed, and a resin composition for film molding was obtained.
[0067] <Method of producing multi-layer film> The dry blended raw materials were fed into the hoppers of three Toshiba Machine single screw extruders (for the front and back layers: 35φmm, L / D=25mm, for the middle layer: 50φmm, L / D=32, for the front and back layers: 35φmm, L / D=25mm), and the extruder temperatures for the outer layer and middle layer were set to 200-230°C. The three-layer structure of the front layer / middle layer / back layer was merged in the feed block and extruded from a 650mm wide T-die (temperature setting 230°C, lip opening 0.5mm). The rotation speed of each extruder was set so that the thickness structure was 9μm / 157μm / 9μm. The extruded molten resin was cooled and solidified on a winding machine equipped with a cooling roll (cooling roll 700 mm wide x φ350 mm, roll temperature approximately 30°C), after which a corona treatment was performed on the side not containing the silicone-olefin copolymer and the resin was wound up to obtain a multilayer film consisting of three types and three layers with a thickness of approximately 175 μm.
[0068] [Film appearance] The surface of the resulting multilayer film on the side of the layer containing the silicone-olefin copolymer was visually observed and evaluated according to the following criteria. ◎: No stains or unevenness are transferred to the film, and the appearance is good ○: The film is slightly dirty or uneven, but still usable. ×: Unusable due to dirt or ejected material adhering to the film
[0069] [Tensile modulus] No. 1 dumbbell test pieces were taken from the resulting multilayer film, and the tensile modulus (MPa) was measured at a tension speed of 50 mm / min using an autograph (Shimadzu Corporation, AGS-X) in an atmosphere of 23°C and 50% RH. The tensile modulus was measured in the extrusion direction (MD) of the film.
[0070] [Tensile elongation at break] No. 1 dumbbell test pieces were taken from the obtained film, and the tensile elongation at break (%) was measured at a tension speed of 300 mm / min using a small tabletop testing machine (EZ-L manufactured by Shimadzu Corporation) in an atmosphere of 23°C and 50% RH. The tensile elongation at break was measured in the extrusion direction (MD) of the film.
[0071] [60° Gloss Value] The resulting multilayer film was used to measure the 60° gloss value of the surface containing the silicone-olefin copolymer using a portable gloss meter (Murakami Color Research Laboratory GMX-203 gloss meter) in accordance with JIS K7105. Table 1 shows the values measured before and after the Gakushin abrasion test described below. The value calculated by the following formula was used as the 60° gloss retention rate before and after the Gakushin abrasion test. TIFF0007604281000002.tif15169
[0072] [Gakushin abrasion test] The obtained multilayer film was set up in a Gakushin-type friction fastness tester manufactured by Tester Sangyo Co., Ltd. so that the side of the layer containing the silicone-olefin copolymer could be tested. Next, referring to JIS K5701-1, a Kanakin No. 3 cotton cloth was attached to the 20 mm square friction element that was in contact with the film, and after applying a load of 500 g, the side containing the silicone-olefin copolymer of the multilayer film was subjected to 10 back and forth strokes (back and forth speed: 3.6 m / min, back and forth distance: 120 mm) to carry out the test. The Gakushin abrasion test was performed in the extrusion direction (MD) of the film.
[0073] [Processability of adhesive film] The resulting adhesive film, which had an adhesive layer provided on the side of the multilayer film that did not contain the silicone-olefin copolymer, was evaluated for workability when attaching it to the exterior of an automobile according to the following criteria. ◎: The film is flexible and easy to work with. ○: The film is flexible enough to be worked with. ×: The film has poor flexibility and is difficult to work with.
[0074] [Weather resistance] The obtained multilayer film was measured using a Metaling Vertical Weather Meter MV3000 (Suga Test Instruments Co., Ltd.) at an irradiance of 0.53 W / m 2 The specimens were subjected to repeated irradiation (63°C, 50%) for 102 minutes and irradiation + rainfall (40°C, 95%) for 18 minutes, and evaluated based on the time it took for the specimens to become embrittled. ○: Treatment time for embrittlement is 300 hours or more △: Treatment time for embrittlement is 200 hours or more but less than 300 hours. ×: Treatment time leading to embrittlement is less than 200 hours
[0075] [Example 1] A linear low-density polyethylene and an olefin-based elastomer were used as the PO-based resins for the front and back layers and the middle layer, and a silicone-olefin copolymer master batch was added as a lubricant on one side of the front and back layers to obtain a multilayer film consisting of three types and three layers containing the silicone-olefin copolymer on one side of the front and back layers. The PO-based resin and lubricant were mixed in the amounts shown in Table 1. The film had no deterioration in appearance due to the silicone-olefin copolymer erupting onto the surface, and had a tensile modulus of elasticity of 200 MPa, and was a film with excellent appearance and flexibility. Furthermore, the 60° gloss value of the side of this multilayer film containing the layer of silicone-olefin copolymer before the Gakushin abrasion test was 93, and after the test it was 74, with the gloss value retention rate before and after the test also being 80%, confirming that the film has excellent scratch resistance and slip resistance. Furthermore, an acrylic adhesive (SK Dyne 1502C manufactured by Soken Chemical Industries, Ltd.) was applied onto the separator using the comma coat method so that the adhesive layer would have a thickness of 25 μm after drying, and then dried for 5 minutes in a hot air dryer at 80°C to form an adhesive layer. The adhesive layer was then bonded to the side of the multilayer film that did not contain the silicone-olefin copolymer to obtain an adhesive film. The separator was peeled off from this adhesive film and applied to the exterior of an automobile. It was confirmed that the film had excellent flexibility, making it easy to apply, and that the film had excellent workability and processability.
[0076] [Example 2] The same procedure as in Example 1 was carried out except that the content of the silicone-olefin copolymer was set to the blending amount shown in Table 1. The film had no deterioration in appearance due to the silicone-olefin copolymer erupting onto the surface, and had a tensile modulus of elasticity of 200 MPa, and was a film with excellent appearance and flexibility. Furthermore, the 60° gloss value of the surface of the layer containing the silicone-olefin copolymer in this multilayer film before the Gakushin abrasion test was 93, and after the test it was 88, with the gloss value retention rate before and after the test also being 95%, demonstrating that the film has excellent scratch resistance and slip resistance. The separator was peeled off from the adhesive film using this multilayer film and attached to the exterior of a car. It was confirmed that the film had excellent flexibility, making it easy to attach, and that the film had excellent workability and processability.
[0077] [Example 3] The same procedure as in Example 2 was carried out, except that the PO resin was replaced with only an olefin elastomer. The film had no deterioration in appearance due to the silicone-olefin copolymer erupting onto the surface, and had a tensile modulus of 230 MPa, exhibiting excellent appearance and good flexibility. Furthermore, the 60° gloss value of the surface of the layer containing the silicone-olefin copolymer in this multilayer film before the Gakushin abrasion test was 93, and after the test it was 88, with the gloss value retention rate before and after the test also being 95%, demonstrating that the film has excellent scratch resistance and slip resistance. The separator was peeled off from the adhesive film using this multilayer film and attached to the exterior of a car. Because the film had good flexibility, it could be attached without any problems, and it was confirmed that the film had sufficient workability and processability.
[0078] [Example 4] The same procedure as in Example 2 was carried out except that the PO-based resin was used in the amount shown in Table 1. The film had no deterioration in appearance due to the silicone-olefin copolymer erupting onto the surface, and had a tensile modulus of elasticity of 200 MPa, and was a film with excellent appearance and flexibility. Furthermore, the 60° gloss value of the surface of the layer containing the silicone-olefin copolymer in this multilayer film before the Gakushin abrasion test was 93, and after the test it was 88, with the gloss value retention rate before and after the test also being 95%, demonstrating that the film has excellent scratch resistance and slip resistance. The separator was peeled off from the adhesive film using this multilayer film and attached to the exterior of a car. It was confirmed that the film had excellent flexibility, making it easy to attach, and that the film had excellent workability and processability.
[0079] [Example 5] The same procedure as in Example 4 was carried out except that the silicone-olefin copolymer was used in the amount shown in Table 1. The film had no deterioration in appearance due to the silicone-olefin copolymer erupting onto the surface, and had a tensile modulus of elasticity of 200 MPa, and was a film with excellent appearance and flexibility. Furthermore, the 60° gloss value of the side of this multilayer film containing the layer of silicone-olefin copolymer before the Gakushin abrasion test was 93, and after the test it was 90, and the retention rate of gloss value before and after the test was also 97%, confirming that the film has excellent scratch resistance and slip resistance. The separator was peeled off from the adhesive film using this multilayer film and attached to the exterior of a car. It was confirmed that the film had excellent flexibility, making it easy to attach, and that the film had excellent workability and processability.
[0080] [Example 6] The same procedure as in Example 4 was carried out except that the silicone-olefin copolymer was used in the amount shown in Table 1. Although the film had slight stains and irregularities due to the silicone-olefin copolymer being sprayed onto the surface, the appearance was good. The tensile modulus of the film was 200 MPa, and the film had good appearance and excellent flexibility. Furthermore, the 60° gloss value of the side of this multilayer film containing the layer of silicone-olefin copolymer before the Gakushin abrasion test was 93, and after the test it was 89, and the retention rate of gloss value before and after the test was 96%, confirming that the film has excellent scratch resistance and slip resistance. The separator was peeled off from the adhesive film using this multilayer film and attached to the exterior of a car. It was confirmed that the film had excellent flexibility, making it easy to attach, and that the film had excellent workability and processability.
[0081] [Example 7] The same procedure as in Example 4 was carried out except that the silicone-olefin copolymer and the olefin-based elastomer were added in the amounts shown in Table 1. Although the film had some stains and irregularities transferred from the silicone-olefin copolymer to the surface, the film had a good appearance. The tensile modulus of the film was 230 MPa, and the film had a good appearance and excellent flexibility. Furthermore, the 60° gloss value of the surface of the layer containing the silicone-olefin copolymer in this multilayer film before the Gakushin abrasion test was 93, and after the test it was 90, with the retention of gloss value before and after the test also being 97%, demonstrating that the film has excellent scratch resistance and slip resistance. The separator was peeled off from the adhesive film using this multilayer film and attached to the exterior of a car. Because the film had good flexibility, it could be attached without any problems, and it was confirmed that the film had sufficient workability and processability.
[0082] [Example 8] The same procedure as in Example 7 was carried out using the random polypropylene, olefin-based elastomer, silicone-olefin copolymer, light stabilizer, and UV absorber in the amounts shown in Table 1. Although the film had some stains and irregularities transferred from the silicone-olefin copolymer to the surface, the film had a good appearance. The tensile modulus of the film was 270 MPa, and the film had a good appearance and excellent flexibility. Furthermore, the 60° gloss value of the surface of the layer containing the silicone-olefin copolymer of this multilayer film before the Gakushin abrasion test was 89, and after the test it was 85. The retention rate of gloss value before and after the test was also 96%, confirming that the film has excellent scratch resistance and slip resistance. This multilayer film had a haze of 2% and was a film with good transparency, since the polyolefin resin used in the masterbatch of the light stabilizer and the masterbatch of the ultraviolet absorbing agent was a polypropylene resin. Because the UV absorbent used is a benzotriazole-based UV absorbent, the weather resistance embrittlement time is approximately 250 hours, and it has been determined that this is not a problem for practical use. In addition, the amount of random polypropylene (B) added to the front and back layers was 80 parts by mass, and the amount of olefin-based elastomer was 20 parts by mass, so that the film formability was improved. The separator was peeled off from the adhesive film using this multilayer film and attached to the exterior of a car. Because the film had good flexibility, it could be attached without any problems, and it was confirmed that the film had sufficient workability and processability.
[0083] [Example 9] The same procedure as in Example 7 was carried out using the random polypropylene, olefin-based elastomer, silicone-olefin copolymer, light stabilizer, and UV absorber in the amounts shown in Table 1. Although the film had some stains and irregularities transferred from the silicone-olefin copolymer to the surface, the film had a good appearance. The tensile modulus of the film was 270 MPa, and the film had a good appearance and excellent flexibility. Furthermore, the 60° gloss value of the surface of the layer containing the silicone-olefin copolymer of this multilayer film before the Gakushin abrasion test was 88, and after the test it was 85. The retention rate of gloss value before and after the test was also 97%, confirming that the film has excellent scratch resistance and slip resistance. This multilayer film had a haze of 2% and was a film with good transparency, since the polyolefin resin used in the masterbatch of the light stabilizer and the masterbatch of the ultraviolet absorbing agent was a polypropylene resin. Since the ultraviolet absorbent used is a triazine-based ultraviolet absorbent, the weather resistance brittle time was 300 hours or more, confirming excellent weather resistance. In addition, the amount of random polypropylene (B) added to the front and back layers was 80 parts by mass, and the amount of olefin-based elastomer was 20 parts by mass, so that the film formability was improved. The separator was peeled off from the adhesive film using this multilayer film and attached to the exterior of a car. Because the film had good flexibility, it could be attached without any problems, and it was confirmed that the film had sufficient workability and processability.
[0084] [Comparative Example 1] The same procedure as in Example 3 was carried out except that the content of the silicone-olefin copolymer was set to the blending amount shown in Table 1. The film had no deterioration in appearance due to the silicone-olefin copolymer being sprayed onto the surface, and had a tensile modulus of elasticity of 230 MPa, and was a film with good appearance and excellent flexibility. Furthermore, the 60° gloss value of the surface of this multilayer film containing the layer containing the silicone-olefin copolymer before the abrasion test was 93, and after the test it was 55, with the retention of gloss value before and after the test also being 59%. It was confirmed that this multi-layer film had poor scratch resistance and slipperiness due to the low content of silicone-olefin copolymer.
[0085] [Comparative Example 2] The same procedure as in Example 3 was carried out, except that the PO-based resin was only random polypropylene. The appearance of this film was good, although some stains and unevenness were observed due to the silicone-olefin copolymer being sprayed onto the surface. The tensile modulus of the film was 600 MPa, and although the film had a good appearance, it had poor flexibility. Furthermore, the 60° gloss value of the surface of the layer containing the silicone-olefin copolymer in this multilayer film before the Gakushin abrasion test was 93, and after the test it was 88, with the gloss value retention rate before and after the test also being 95%, demonstrating that the film has excellent scratch resistance and slip resistance. When the separator was peeled off from the pressure-sensitive adhesive film using this multilayer film and attached to the exterior of an automobile, it was confirmed that the film had poor flexibility, resulting in inferior followability to the shape of the automobile exterior, as well as poor workability and processability.
[0086] [Comparative Example 3] The procedure of Example 4 was repeated, except that the slip agent masterbatch was used as the lubricant in the blending amounts shown in Table 1. It was confirmed that this film was inferior in appearance from the time when ejection of fatty acid amide contained in the slip agent masterbatch onto the surface was confirmed and whitening of the film occurred due to this.
[0087] [Table 1]
[0088] [Example 10] The ink manufactured by DIC Graphics Co., Ltd. described below was applied to the side of the multilayer film obtained in Example 1 that did not contain the silicone-olefin copolymer using the gravure printing tester "GP-2" manufactured by Kurashiki Boseki Co., Ltd. and the printing plate "54L gradation". The film after application was aged at 40°C for 5 days to obtain a decorative film with a printed layer formed by the ink.
[0089] [Ink manufactured by DIC Graphics Co., Ltd.] An ink was prepared by mixing 95 parts by mass of "VTP-NT40 Yellow (A)" and 5 parts by mass of "AT-NT Solvent" and stirring. "VTP-NT40 Yellow (A)": A paint composed of a mixture of a vinyl chloride / vinyl acetate copolymer and an acrylic resin and methyl isobutyl ketone as a solvent. "AT-NT Solvent": A mixture of butyl acetate / ethyl acetate / methyl ethyl ketone
[0090] Further, a decorative adhesive film was obtained by laminating an adhesive layer on the printed layer of the obtained decorative film by the method described in Example 1. The separator was peeled off from the decorative adhesive film and attached to the exterior of an automobile. Since the film had excellent flexibility, it was easily attached to the exterior of an automobile. Therefore, it was confirmed that the decorative adhesive film had excellent workability and processability. [Industrial Applicability]
[0091] By using a film having a layer made of the resin composition of the present invention, a polyolefin resin film having excellent scratch resistance, flexibility, and conformability to a molded body having a three-dimensional shape can be obtained. In addition, by laminating an adhesive layer or a printed layer on the film, an adhesive film or a decorative film can be obtained, and these films can be suitably used for automotive decorative purposes.
Claims
1. A multilayer film having a plurality of layers containing a polyolefin resin, a layer made of a resin composition containing 0.20 parts by mass or more of a silicone-olefin copolymer per 100 parts by mass of a polyolefin resin, on at least one of the front and back surfaces; The multilayer film has a tensile modulus of 400 MPa or less, In at least one layer of the multilayer film, the proportion of the olefin-based elastomer in the polyolefin-based resin is 50 parts by mass or more, In the layer made of the resin composition, the proportion of the olefin-based elastomer in the polyolefin-based resin is 5 to 50 parts by mass. The multi-layer film.
2. A multilayer film as described in claim 1, comprising at least a surface layer, an intermediate layer and a back layer, wherein the proportion of the olefin-based elastomer in the polyolefin-based resin of the surface layer and the back layer is 1 part by mass or more and 80 parts by mass or less, the proportion of the olefin-based elastomer in the polyolefin-based resin of the intermediate layer is 50 parts by mass or more and 100 parts by mass or less, and at least one of the surface layer and the back layer is a layer made of a resin composition containing 0.20 parts by mass or more of silicone-olefin copolymer per 100 parts by mass of polyolefin-based resin.
3. 3. The multilayer film according to claim 1, wherein the silicone-olefin copolymer is a silicone-olefin copolymer masterbatch containing the silicone-olefin copolymer.
4. The multilayer film according to any one of claims 1 to 3, characterized in that it is composed of at least two layers.
5. 5. The multilayer film according to claim 1, wherein the polyolefin resin comprises one or more of a polyethylene resin, a polypropylene resin, and an olefin elastomer.
6. The multilayer film according to any one of claims 1 to 5, characterized in that the 60° gloss value after a Gakushin abrasion test is 60 or more.
7. 7. A pressure-sensitive adhesive film comprising the film according to claim 1, and an adhesive layer laminated on a surface of the film other than the layer made of the resin composition containing the silicone-olefin copolymer.
8. A decorative film comprising the film according to any one of claims 1 to 6, and a printed layer laminated on a surface of the film other than the layer made of the resin composition containing the silicone-olefin copolymer.
9. A decorative adhesive film comprising the decorative film according to claim 8 and an adhesive layer further laminated on the printed layer side of the decorative film.
10. A protective film for automobiles using the film according to any one of claims 7 to 9.
Citation Information
Patent Citations
JP1976012646A
Decorative sheet
JP1999129420A
Laminate film made of polyolefin-based resin
JP2004002825A
Polyolefin-based laminated film and adhesive film
JP2007083530A
Water-repellent film
JP2015024548A
